Titanium compacts produced by the pulvimetallurgical hydride-dehydride method for biomedical applications - Barreiro, M. M. (2010)
Titanium powder production by the hydride-dehydride method has been developed as a non-expensive process. In this work, commercially pure grade two Ti specimens were hydrogenated. The hydrided material was milled in a planetary mill. The hydrided titanium powder was dehydrided and then sieved to obtain a particle size between 37 and 125 νm in order to compare it with a commercial powder produced by chemical reduction with a particle size lower than 150 νm. Cylindrical green compacts were obtained by uniaxial pressing of the powders at 343 MPa and sintering in vacuum. The powders and the density of sintered compacts were characterized, the oxygen content was measured and in vivo tests were performed in the tibia bones of Wistar rats in order to evaluate their biocompatibility. No differences were observed between the materials which were produced either with powders obtained by the hydride-dehydride method or with commercial powders produced by chemical reduction regarding modifications in compactation, sintering and biological behaviour.